The Effect of Augmented Reality-Assisted Problem Based Learning on Mathematical Reasoning Ability - Khairunnisa, Rika; Faradillah, Ayu (Jurnal Pendidikan Progresif, 2023)
The Effect of Problem-Based Learning (PBL) Models Assisted Augmented Reality (AR) on Mathematical Reasoning Ability. Objectives: This study aimed to determine the effect of Problem-Based Learning (PBL) models-assisted Augmented Reality (AR) on mathematical reasoning abilities (MRA). Methods: This study used a quasi-experimental post-test-only control group research design. The population of this research was class X in senior high school Jakarta and the research sample consisted of 34 students in the experimental class and 36 students in the control class who were selected using a purposive sampling technique. The research instrument was a description test analyzed using IBM SPSS 27 and Winstep, Findings: The findings indicate a significant difference between the experimental and control classes with the Mann-Whitney U-test Asymp. Sig. 0.00 (H0 denied). While the results of Cohen's d effect size were obtained at d = 1.54, meaning that the PBL models-assisted AR was classified as very large, where students in the experimental class were better than the control class. Furthermore, the Wright maps that the percentage of MRA is high (14%), medium (76%) and low (10%), Conclusion: Students who receive the application of the PBL models-assisted AR become more active, able to solve given contextual problems well and are more innovative in expanding their knowledge related to mathematical material. Therefore, the application of the PBL models-assisted AR affects MRA. Keyword: PBL, AR, mathematical reasoning ability.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202352